Struktur Komunitas Kupu-Kupu Superfamili Papilionoidae (Lepidoptera) di Kawasan DAS Budi Kecamatan Sungai Betung Kabupaten Bengkayang Provinsi Kalimantan Barat - Diba, Farah; Ressiawan, R; Nurhaida, N (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2021)
The Budi watershed, which is located in Sungai Betung Subdistrict, Bengkayang Regency, West Kalimantan Province, is a land and water conservation area which is a source of clean water for the community. The forest in the Budi watershed becomes a habitat for butterflies. The research aims to analyze the community structure and identify the types of butterflies in Budi watershed Sungai Betung Subdistrict, Bengkayang Regency, West Kalimantan Province. The research methods used survey method with scan sampling technique in the morning and evening. Data from the inventory of butterfly species and the number of individuals of each species were analyzwd using the Shannon-Wiener diversity index (Hâ€), the Margalef species richness index (DMg) and the Simpson dominance index (D). The results showed that the total number of butterfly species found in the Budi watershed was 22 species with 148 individuals belonging to three families, namely Nymphalidae (14 species), Papilionoidae (3 species), and Pieridae (5 species). The most dominance species found were Eurema blanda, Hypolimnas bolina, and Letopsia nina. The index of butterfly species richness in Budi watershed was DMg = 9.67 and is included in categorized high species richness. The butterfly dominance index D = 0.0066 and it categorized to low species dominance. Species diversity index Hâ€ = 2.093 and showed the diversity of butterfly species in the Budi watershed, Sungai Betung sub district, Bengkayang Regency is included in the medium diversity category. Â